2011
DOI: 10.1093/jac/dkr451
|View full text |Cite
|
Sign up to set email alerts
|

Population structure, virulence potential and antibiotic susceptibility of uropathogenic Escherichia coli from Northwest England

Abstract: ST131 isolates are well established in the wider UPEC population. This clone is still evolving and we further support suggestions that it represents a real threat to health. We suggest that ST127 is a recently emerged, community-associated, virulent clone that warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
174
4
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(204 citation statements)
references
References 44 publications
25
174
4
1
Order By: Relevance
“…29 Over the last decade, the ST131 virulent pandemic clone has emerged in hospitals and in the community worldwide, causing outbreaks of MDR infections across the globe. 30 It has been frequently described as a urinary pathogen in humans, 31 and a fatal case of urosepsis associated with a multi-resistant strain of E. coli ST131 was reported recently 30 Although rarely isolated from companion animals, a recent report found E. coli ST131 to distribute among human and animal household members in Australia, suggesting serious clinical and public health implications. 32 In Europe, until now, ST131 has only been isolated from dogs, horses, 33 poultry 34 and pigs 35 .…”
Section: Discussionmentioning
confidence: 99%
“…29 Over the last decade, the ST131 virulent pandemic clone has emerged in hospitals and in the community worldwide, causing outbreaks of MDR infections across the globe. 30 It has been frequently described as a urinary pathogen in humans, 31 and a fatal case of urosepsis associated with a multi-resistant strain of E. coli ST131 was reported recently 30 Although rarely isolated from companion animals, a recent report found E. coli ST131 to distribute among human and animal household members in Australia, suggesting serious clinical and public health implications. 32 In Europe, until now, ST131 has only been isolated from dogs, horses, 33 poultry 34 and pigs 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous genetic studies of E. coli lineages associated with UTI and/or bacteremia in England and the US have reported that the most prevalent multilocus sequence types (MLSTs) are sequence types (STs) ST73, ST131, ST95, and ST69 (Gibreel et al 2012;Adams-Sapper et al 2013;Alhashash et al 2013;Banerjee et al 2013;Horner et al 2014). ST131 has received particular attention, following its apparent emergence in the 2000s, due to its rapid global dissemination and frequent multidrug-resistant (MDR) phenotype (Nicolas-Chanoine et al 2014).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Among VF genes, iroN and sfa were significantly more present in VAP isolates than colonization isolates (Table 3). Further characterization of the 16 VAP B2 isolates showed that only two belonged to the frequently recovered subgroup II [multilocus sequence type complex (STc)73)] [27]. Of note, five isolates from four patients belonged to subgroup III (STc127), which encompasses the highly virulent archetypal strain 536 [26] (Table 4).…”
Section: Phylogenetic Groups and Vf Genesmentioning
confidence: 99%